PERMAINAN TRADISIONAL HEDAROJI PADA MASYARAKAT KELURAHAN WANCI KECAMATAN WANGI-WANGI KABUPATEN WAKATOBI - Sidik, Wa Ode Islamia; Nurtikawati, Nurtikawati; Suraya, Rahmat Sewa; Basri, La Ode Ali (Universitas Halu Oleo, 2020)
This research aims to analyze the functions and values contained in the hedaroji game as one of the traditional games of the Wanci people in the past which are now becoming extinct. Data collection was carried out through in-depth interviews, involved observation, and discussion. Data were analyzed through analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The results showed that in the past the traditional game of, hedaroji served as people's entertainment, a gathering place and to strengthen the sense of kinship, and as an effort to pass the culture on to the next generation of traditions. In the traditional game, hedaroji contains sportsmanship, educational values, and religious values. Keywords: traditional games, hedaroji, function, values and marginalizationÂ